Evaluating The Feasibility Of CO2 Storage Through A Geomechanical Approach : A Case Study Of The Talang Akar Formation, Crestal Area Of Asri Basin, LUF Well - Lathifah, Lista Ummu Fadzilatul; Muslin, Dicky; Muljana, Budi; Laranarko, Dwandari; Santosa, Ardian Aby (Bulletin of Scientific Contribution, 2025)
Asri Basin is one of Indonesia’s sedimentary basins, and it is the carbon dioxide storage target in Carbon Capture Storage (CCS) technology. A study of carbon dioxide storage containers must be carried out based on geological aspects, namely geological and rock conditions. This research aims to identify reservoir feasibility values in the Asri Basin, such as pore pressure and fracture pressure, along with other factors affecting reservoir stability, in order to minimize leakage during the carbon dioxide injection process. The identification process in this research uses quantitative and qualitative studies based on well data. Eaton's method was used to estimate the research well pore pressure and fracture pressure in the research wells. The research well is located in the crestal area of the Asri Basin and has a pore pressure with a normal pressure trend. The fracture pressure value gets smaller in the depth range of the Talang Akar Formation. There is a process of diagenesis of the clay mineral smectite into illite, which begins to be found at a depth of 3000 - 3500 ftTVDSS. The developed stress regime is a normal stress regime with the vertical stress value as the largest. The injection process in the Asri Basin can be carried out in the Talang Akar Formation with several five storage intervals at a depth of 3560 - 4130 ftTVDSS.